2019
DOI: 10.1021/acs.chemrestox.8b00328
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis in Acute Paraquat Poisoning Patients Based on UPLC-Q-TOF-MS and Machine Learning Approach

Abstract: Most paraquat (PQ) poisoned patients died from acute multiple organ failure (MOF) such as lung, kidney, and heart. However, the exact mechanism of intoxication is still unclear. In order to find out the initial toxic mechanism of PQ poisoning, a blood metabolomics study based on ultraperformance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) and efficient machine learning approach was performed on 23 PQ poisoned patients and 29 healthy subjects. The initial PQ plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In future work, the proposed method can be further used to diagnosis or prognosis of paraquat-poisoned patients [104]- [109], identification of poisoning status [110]- [112], diagnosis of tuberculous pleural effusion [113], differentiation of malignant and benign thyroid nodules [114], early diagnosis of Parkinson's disease [115]- [119], RNA secondary structure prediction [120], detection of erythemato-squamous diseases [121], online recognition of foreign fibers in cotton [122].…”
Section: Discussionmentioning
confidence: 99%
“…In future work, the proposed method can be further used to diagnosis or prognosis of paraquat-poisoned patients [104]- [109], identification of poisoning status [110]- [112], diagnosis of tuberculous pleural effusion [113], differentiation of malignant and benign thyroid nodules [114], early diagnosis of Parkinson's disease [115]- [119], RNA secondary structure prediction [120], detection of erythemato-squamous diseases [121], online recognition of foreign fibers in cotton [122].…”
Section: Discussionmentioning
confidence: 99%
“…15 Dong et al investigated ML to predict opioid overdose, and found high recall using a random forest model and high accuracy with deep learning models. 22 Other studies have leveraged ML to predict paraquat poisoning prognosis, 23,24 seizures from tramadol poisoning, 25 adverse drug events in elderly patients, 26 smoking cessation treatment outcome, 27 lead poisoning in children, 28 pesticide ototoxicity 29 and inadequate medication responses in the emergency department. 30 In recent years, ML in medicine has garnered considerable interest, from anticipated cost-effectiveness, speed, and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…It has significant advantages such as a high sensitivity, fast analysis speed, and high-resolution separation. There are a few papers that applied UHPLC–MS for the detection of PQ and DQ in biological samples [ 13 , 32 , 42 , 69 , 70 ]. Lu et al obtained LODs of 0.1 and 0.3 ng/mL and LOQs of 0.3 and 0.8 ng/mL for urine and plasma by UPLC–ESI–HRMS/MS, respectively [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Commonly used HRMS detectors include orbitrap MS, ion trap, time-of-flight mass spectrometry (TOF MS), and FTICR. FTICR/MS has an extremely high resolution, but its high data acquisition speed limits its on-line coupling with UPLC [ 68 , 69 , 70 , 71 ]. Time-of-flight mass spectrometry has innate performance advantages over quadrupole mass spectrometers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation